Integrated Fire Safety Solution: A Microcontroller-Based Fire Alarm and Pull-Activated Fire Extinguisher System for Science Laboratory Environment - Rosman, Muhammad Ruzaini; Sumaiya Mashori, (Progress in Engineering Application and Technology, 2024)
Fire hazards in science labs endanger students, staff, and research. Traditional fire alarm systems delay detection and response, increasing damage and risk. Scientific lab fire safety rules need an advanced fire safety system with accurate flame detection, gas leakage sensing, and real-time communication. This research project creates an Arduino Uno Rev 3-based fire alarm system. This project quickly responds to gas leaks and flames. Arduino Uno is the microcontroller. It talks to flame, gas, siren, warning light, LCD, and GSM modules. Flame sensors detect fires, gas sensors detect laboratory gas leaks. Fires and gas leaks activate the microcontroller's alarm and warning light. GSM modules notify and support users. Hardware development comprises interfacing controllers, checking sensors for accuracy, and integrating system components. Software development incorporates microcontroller programming for sensor inputs, alarms, and LCD displays. Pull-Activated fire extinguishing makes the Integrated Fire Safety Solution proactive and efficient. Toggle switches activate power windows and Pull-Activated systems. This technology detects early stages and helps users and managers address concerns. A Pull-Activated System should be built to enhance functionality.